PENERAPAN DISCOVERY LEARNING BERBANTUAN PhET SIMULATIONS UNTUK MENINGKATKAN HASIL BELAJAR LISTRIK STATIS DI SMA - Tio Ramadhan; Tomo Djudin; Hamdani Hamdani (Universitas Tanjungpura, 2020)
AbstractThe aim of this research was to improve students’ performance in electrostatic to year-12 of SMA Negeri 3 Pontianak in the academic 2019/2020 through discovery learning that aided by using PhET simulation. The methods and forms of research those are experimental and quasi experimental nonequivalent control group. The sample was students XII IPA 3 as an experimental class and XII IPA 4 was the control class which drawn by using intact group random sampling technique. The instrument used 10 multiple choice questions, 4 essay questions, and 20 students attitude questionnaires. The result showed that students’ score in experimental class at pretest and posttest had average of 22.97 and 59.06, while in control class are 23.17 and 53.51. There was a significant difference between students’ learning outcome in experimental class and conventional class (t=2.16, P < 0.05), after learning activities; (3) The effectiveness discovery learning with PhET simulations is ES=0,51 (medium classified) of increased learning outcome compared with conventional learning; (4) Student attitudes towards discovery learning with PhET simulations was 78,50% (good category). Discovery learning with PhET simulations is expected to be used as an alternative to improve on students’ learning outcome especially in other physics lessons.Keywords: Discovery Learning, Electrostatic, Learning Outcome, PhET Simulations